Validation of the Informal Caregiver Burden Assessment Questionnaire for Brazil - short version - Elaine Trevezanuto Correia; Anderson da Silva Rêgo; Marcelo da Silva; Rafaely de Cássia Nogueira Sanches; Eraldo Schunk Silva; Daniela Milani; Cremilde Aparecida Trindade Radovanovic (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to cross-culturally adapt the short version of the Informal Caregiver Burden Assessment Questionnaire to the Brazilian culture and test its psychometric properties. Methods: the questionnaire was translated, adapted, and applied to a sample of 280 informal caregivers. The psychometric assessment was verified by estimating psychometric sensitivity and internal structure validity. Results: inter-rater agreement was satisfactory among specialists. In the seven-factor model, item (Q9) of the domain "Perception of Efficacy and Control Mechanisms" showed a factor loading less than 0.40 (ʎ = 0.26), and an alternative six-factor model was evaluated. However, both models showed excellent fit indices, and it was decided to keep the seven-factor reference model. Reliability was satisfactory for the seven subscales (α > 0.70). Conclusions: the questionnaire was adapted and showed adequate psychometric indices in the Brazilian context in which it was evaluated, preserving its original essence.